2022
DOI: 10.1017/s0008423922000324
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Promise and Performance of Agencies in the Government of Canada

Abstract: Canada has not escaped trends in most liberal democracies with the rapid growth of agencies created by government to deliver public goods, often justified on elements of their mandate—service delivery, adjudication of disputes, regulatory oversight, among others—benefiting from an arm's-length relationship to the government of the day. Yet Canadian studies of this phenomenon remain mostly absent from the robust comparative literature theorizing and documenting the emergence of widespread “agencification” and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Canada has indeed “agencified” in recent decades, but we have little basis to make claims about trends in how they perform across various functions and over time. By drawing on the Government of Canada's Public Service Employee Survey (PSES) microdata from 1999, 2005, 2011, and 2017, building off Doberstein (2022), we are able to isolate and compare employee experiences in departments versus agencies on key metrics of agencification like climate of innovation, employee autonomy, and organizational efficiency. The main finding that emerges from this data spanning nearly twenty years is that those working in enforcement agencies are exhibiting few of the purported advantages of agencification: they are not displaying a particularly innovative organizational climate, employees in the organization report less autonomy than those in departments, and there are no indications from employees that the organizations are more efficient than departmental counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Canada has indeed “agencified” in recent decades, but we have little basis to make claims about trends in how they perform across various functions and over time. By drawing on the Government of Canada's Public Service Employee Survey (PSES) microdata from 1999, 2005, 2011, and 2017, building off Doberstein (2022), we are able to isolate and compare employee experiences in departments versus agencies on key metrics of agencification like climate of innovation, employee autonomy, and organizational efficiency. The main finding that emerges from this data spanning nearly twenty years is that those working in enforcement agencies are exhibiting few of the purported advantages of agencification: they are not displaying a particularly innovative organizational climate, employees in the organization report less autonomy than those in departments, and there are no indications from employees that the organizations are more efficient than departmental counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…This study uses a unique data set from the Government of Canada to build on the effort of Doberstein (2022) to paint a bigger picture, using quantitative data, on agencification in Canada. Drawing on comparative agencification research identified in the literature above, this study examines the following hypotheses with respect to agencies in Canada over time:…”
Section: The Emerging Canadian Story Of Agenciesmentioning
confidence: 99%